Monitoring of performance of the municipal wastewater treatment facilities - Shandrovych, Vira; Malovanyy, Myroslav (Lviv Polytechnic Publishing House, 2015)
The paper has engaged monitoring of performance of the municipal wastewater treatment facilities of Lviv by analyzing the average monthly data of their operation, obtained in a chemico-bacteriological laboratory of the Lviv City Utility Enterprise "Lvivvodokanal". Also, performance of aerotanks of the same facilities has been studied by carrying out check measurements of the concentration of dissolved oxygen and ammonium in them.
Keywords: monitoring; wastewater treatment facilities; dissolved oxygen; aerotanks; active sludge